2018
DOI: 10.1111/jam.13894
|View full text |Cite
|
Sign up to set email alerts
|

Screening of white‐rot fungi for bioprocessing of wheat straw into ruminant feed

Abstract: Large variation exists within and among different fungal species in the valorization of wheat straw, which offers opportunities to improve the fungal genotype by breeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 62 publications
(90 citation statements)
references
References 43 publications
7
81
1
1
Order By: Relevance
“…To facilitate further understanding, we compared the two methods based on the relationship of cell wall contents with ruminal digestibility, as measured by the IVGP . The changes in IVGP of these fungal‐treated straws have been previously discussed in detail – hence, will only be mentioned briefly. All fungi clearly increased the IVGP of the wheat straw (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To facilitate further understanding, we compared the two methods based on the relationship of cell wall contents with ruminal digestibility, as measured by the IVGP . The changes in IVGP of these fungal‐treated straws have been previously discussed in detail – hence, will only be mentioned briefly. All fungi clearly increased the IVGP of the wheat straw (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…From ruminant perspective, ruminal digestibility – assessed either by in vitro , in situ or in vivo technique, is the most effective technique to select the best fungi for improving the nutritive value of wheat straw . To explain the changes in the digestibility, Method A should be used.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to ligninolytic enzymes, certain whiterot fungi also produce cellulose-degrading enzymes (β-glucosidase, cellobiohydrolase, and β-xylosidase; Vrsanska et al, 2016), resulting in simultaneous degradation of lignin and cellulose components by several strains (Trametes versicolor, Heterobasidium annosum, and Irpex lacteus). Consequently, white-rot fungi can improve digestibility and nutritive value of low-quality forages such as wheat straw and bermudagrass (Akin et al, 1993;Nayan et al, 2018). Tuyen et al (2012) reported that 9 of 11 species of white-rot fungi increased IVNDFD and in vitro ADF digestibility of wheat straw.…”
Section: White-and Brown-rot Fungimentioning
confidence: 99%